A novel fiber treatment applied to woven jute fabric/vinylester laminates - Stocchi, Ariel Leonardo (2007)
In this work, a novel fiber treatment consisting on an alkali treatment superimposed to biaxial tensile stress was successfully applied to woven jute fabric/vinylester laminates. The effect of treatment on the composites tensile properties was investigated at two different times of treatment. A significant improvement in stiffness was achieved by the composite treated with alkali under stress for 4 h. However, no significant differences between the stiffness of the untreated composite and the composites treated with alkali under stress for 24 h were found. On the other hand, irrespectively of the time of treatment, the composites with fabrics treated with alkali under stress showed the highest values of tensile strength. From results of fabrics tensile tests, compression shear tests and X-ray diffraction analysis, the improved tensile properties exhibited by the composites with treated fabrics could be attributed to structural changes of the fibers as well as to a change in the fiber/matrix interfacial properties.